2021
DOI: 10.1371/journal.pone.0260411
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion interventions for the control of hypertension in Africa, a systematic scoping review from 2011 to 2021

Abstract: Background A proportion of hypertension patients live in developing countries with low awareness, poor control capabilities, and limited health resources. Prevention and control of hypertension can be achieved by applying both targeted and population-based health promotion interventions. This study synthesised the health promotion interventions for the control of hypertension in Africa. Methods An in-depth search of PubMed, CINAHL, EMBASE, Cochrane library, web of science, google scholar yielded 646 titles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
(139 reference statements)
0
9
0
Order By: Relevance
“…Prior intervention studies included another modality, for example, health education or health promotion to promote healthy lifestyle and reduce BP in patients in developing countries. [ 34 , 35 , 36 , 37 ] One intervention in developing countries concluded that mobile health interventions can be used as an effective method for hypertension self-management in patients treated at public hospitals. [ 38 ] Further study on a larger sample is needed to assess the psychometric properties of the Arabic version of the H-SCALE including evaluation of construct, convergent, and discriminant validity in addition to test–retest reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Prior intervention studies included another modality, for example, health education or health promotion to promote healthy lifestyle and reduce BP in patients in developing countries. [ 34 , 35 , 36 , 37 ] One intervention in developing countries concluded that mobile health interventions can be used as an effective method for hypertension self-management in patients treated at public hospitals. [ 38 ] Further study on a larger sample is needed to assess the psychometric properties of the Arabic version of the H-SCALE including evaluation of construct, convergent, and discriminant validity in addition to test–retest reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The self-care and home management of hypertension, like other chronic diseases, involve various behavioral changes that require optimal and effective medication adherence, self-efficacy, and prevention of complications [6,8,17]. Recent systematic reviews on self-care management of hypertension focused on the use of electronic-based technologies [18,19,20], the influence of self-care efficacy [6], and health promotion interventions for the prevention of hypertension [16,17,21]. However, to the best of our knowledge, no systematic review in recent times has specifically focused on the factors that influence home-based and self-care management of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, necessary to identify those young individuals who are at high-risk to implement the necessary intervention strategies for the early prevention of CVD. It is believed that these strategies are sufficient models for tackling CVD through prevention and health promotion, aimed at altering an individual’s lifestyle and behavioural habits [ 8 ]. Several meta-analyses for the prevention of hypertension found that interventions to reduce salt intake [ 9 ] and encourage weight loss through physical activity [ 10 ] and a low-calorie diet [ 11 ] showed small statistical reductions in BP over time.…”
Section: Introductionmentioning
confidence: 99%